Japanese Exclusion and Environmental Conservation in the BC Salmon Fisheries, 1900-1930. Issue 3 (17th May 2022) - Bryce, Benjamin
Abstract: Between 1900 and 1930, fishermen, cannery workers, investors, fisheries officials, and federal commissioners in British Columbia knew that the salmon in the Fraser and Skeena Rivers were overfished. They saw the solution in hatcheries, controlling when and where people could fish, and limiting the number of fishermen engaged in the commercial fisheries. Yet while the first two solutions relied on a certain scientific logic, the last issue was highly influenced by racial ideologies. In the immediate aftermath of Canada's 1908 Gentlemen's Agreement with Japan and with greater force after the First World War, the government and white nationalists sought to curtail the presence of Japanese immigrants and Canadians of Japanese heritage in the BC salmon fisheries. They explicitly described their goals as a strategy for fish conservation and as a way to make the fisheries more accessible to white fishermen. This article shows that local contingencies made the workforces and racial anxieties different not only in BC and California or in Alaska and Hawai'i, but also on the southern and northern coasts of the same province. Merging the often-separate histories of environment and Asian exclusion, this article argues that between 1900 and 1930, government policies in British Columbia aimed at conservation and public concerns about resource depletion were infused with racial ideologies. It demonstrates how state efforts to regulate the fishing industry, and more specifically human responses to changing environmental conditions, became highly linked with the anti-Asian agitation that had already taken hold on the Pacific coast of North America.